Zinc-solubilising rhizobacteria bioformulations in rice systems: Mechanisms, bioformulation strategies and implications for long-term soil health and nutrient - K M Abinash; D Shilpee; M C Mamata; K S Chinmaya; P Madhusmita; P Chinmay; M Ayesha; K S Ranjan; T Snehasish; M Santanu (Plant Science Today, 2026)
Zinc (Zn) deficiency in soils poses a serious threat to global food and nutritional security, especially in developing countries where unsustainable farming, like imbalanced fertiliser use, nutrient mining and organic matter loss, is widespread. In India, surveys of over 242000 soil samples across 615 districts reveal widespread micronutrient deficiencies: 51.2 % for Zn, 58.6 % for sulfur (S) and 44.7 % for boron (B). Common combined deficiencies such as Zn + S (9.3 %), Zn + B (8.7 %) and Zn + iron (Fe) (5.8 %) vary spatially across agro-ecological zones. These findings highlight the urgent need for site-specific integrated nutrient management tailored to diverse soils and crops. Conventional Zn biofortification methods using ZnSO₄ or Zn-chelates have shown benefits but face limitations including high costs, poor adoption and reduced efficacy in acidic soils prevalent in eastern India. Alternatively, microbiological biofortification with Zn-solubilising bacteria (ZSB) offers a sustainable, low-cost solution. ZSB transform insoluble Zn into plant-available forms through mechanisms like chelation, organic acids and siderophore production, enhancing Zn uptake, grain quality and yield. This approach supports sustainable agriculture by improving nutrient use efficiency, reducing chemical inputs and promoting soil microbial health. In acid soils of Odisha, deploying effective ZSB strains offers a promising route to improve soil fertility and combat hidden hunger by boosting micronutrient content in crops. This review synthesises current understanding of ZSB-mediated Zn mobilisation and their application in sustainable Zn biofortification of rice-based systems, particularly in Zn-deficient regions and highlights key research priorities for translating laboratory insights into reliable field-scale outcomes.